Building customer's brand awareness through social media platform - Pastini, Ni Wayan; Lilasari, Luh Nyoman Tri (Journal of Commerce, Management, and Tourism Studies, 2023)
The purpose of this research is to find out how the company, especially in the marketing division, builds customer brand awareness so that customers can recognize the company's products. Brand awareness is the first step to creating brand equity, where brand awareness refers to whether consumers can remember or recognize a brand, and brand awareness is related to the strength of the presence of a brand in consumers' memories. Brand awareness can be related to the cognitive aspect of consumers, where the more a brand can be remembered by consumers, the higher the level of brand awareness. Building brand awareness is important because before consumers buy a product, consumers will first recognize the brand of a product, especially for products that have high value. In the market, there are many companies that provide accommodation. By recognizing a particular brand of accommodation product, potential consumers' interest in buying a product that is already in their memory will be higher. This research is qualitative descriptive research where data is obtained directly as primary data using interview guides with several marketing staff, and observation. Meanwhile, secondary data was obtained from library sources both in the company and from online sources. All data is then collected, data reduction is carried out, tables are made, and analyzed and conclusions are drawn. The research results show that marketing really cares about Indonesia's demographic map, where more than 60% are millennials and Generation Z, where they are very connected to social media. There are several social media platforms used by marketing parties to build brand awareness, such as Instagram, TikTok, Facebook, YouTube, and WhatsApp, but there are indications that Instagram and TikTok are the platforms that are more popular with potential consumers.